Робастное управление стендом двухмассовой электромеханической системы - Кузнецов, Борис Иванович; Никитина, Татьяна Борисовна; Бовдуй, Игорь Валентинович; Волошко, Александр Валерьевич; Виниченко, Елена Владимировна (НТУ "ХПИ", 2010)
This article deals with the mathematical model and robust control for two-mass electromechanics system imitation stand. The example of dynamic characteristics for such system is given.
Robust control for two-mass electromechanics system imitation stand
Keywords: характеристики динамические; регулятор; система синтезированная; обеспечение программное